2006
DOI: 10.1291/hypres.29.905
|View full text |Cite
|
Sign up to set email alerts
|

Oral Pretreatment with Ebselen Enhances Heat Shock Protein 72 Expression and Reduces Myocardial Infarct Size

Abstract: Reactive oxygen species (ROS) enhance myocardial ischemia-reperfusion (I/R

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 45 publications
2
17
0
1
Order By: Relevance
“…Oral intake pretreatment with ebselen enhances HSP72 expression and reduces ROS induced by I/R injury (Baljinnyam et al 2006). To determine if increased levels of HSP70 might contribute to the induction of antioxidant pathways, which detoxify ROS, we measured the activities of antioxidant enzymes and lipid peroxidation in heart homogenates.…”
Section: Discussionmentioning
confidence: 99%
“…Oral intake pretreatment with ebselen enhances HSP72 expression and reduces ROS induced by I/R injury (Baljinnyam et al 2006). To determine if increased levels of HSP70 might contribute to the induction of antioxidant pathways, which detoxify ROS, we measured the activities of antioxidant enzymes and lipid peroxidation in heart homogenates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that E could protect organs such as intestine, neurons, lungs, and myocardium against IRI. 6,[30][31][32] Taken together, E plays an important role in protection of kidneys against IRI experimentally. It may be a good candidate to prevent IRI in kidney transplantations but further studies should be conducted to evaluate its safety and efficacy in humans.…”
Section: Mda (Nmol/g-protein)mentioning
confidence: 98%
“…Particularly, the effects of oral administration of ebselen on experimental MI were examined by Baljinnyam et al [104] and quite remarkably, the enhancement of infarct size with H 2 O 2 was significantly attenuated in the ebselen30 group (P \ 0.01), and it was totally abolished in the ebselen100 group (P \ 0.05). It is also worth mentioning the decrease in myocardial 8-hydroxydeoxyguanosine (8-OHdG) levels as well as the increase in glutathione (GSH) levels after ebselen treatment.…”
Section: Novel Agentsmentioning
confidence: 98%